DESAIN KONSEPTUAL PERISAI BIOLOGI IRRADIATOR GAMMA Co-60 - Sutomo Sutomo; Petrus Zakaria; Edy Karyanta (BATAN, 2012)
A conceptual design of biological shielding for Co-60 gamma irradiator having capacity of 200 kCi has been performed. Based on the available requirements, the shielding material used for irradiation chamber is normal concrete and the irradiation chamber is designed such that the distance between source (when being used) and wall is 3.5 m. The structure of the building is designed in cube of 7 m × 10 m × 4 m. Normal concrete is concrete using raw material of portland cement, coarse and fine aggregate plus water. The concrete density ranges from 2200 to 2500 kg/m3.For this design, the concrete density selected is 2350 kg/m3, considering the ease of procuring the raw material needed as defined by the decree of Bapeten chairment No.11/Ka-Bapeten/VI-99, in order to make exposure doses less than 0,25 mR/hour, the concrete shielding thickness has to be 1.5 m. Desain Konseptual Perisai Biologi Irradiator Gamma Co-60 kapasitas 200 kCi telah dilakukan. Berdasarkan persyaratan yang ada, bahan perisai ruang irradiasi yang dipilih adalah beton normal dan ruang irradiasi didesain dengan ketentuan jarak sumber (saat sedang digunakan) terhadap dinding dan atap 3,5 m. Desain bangunan ini berbentuk kubus atau kotak dengan ukuran 7 m x10 m x4 m. Beton normal adalah beton dengan bahan baku semen portland, agregat kasar dan halus, serta air. Beton ini memiliki berat jenis berkisar 2200 – 2500kg/m3. Desain ini memilih berat jenis beton 2350kg/m3 karena pertimbangan kemudahan untuk mendapatkan bahan baku yang dapat mencapai nilai di atas agar dosis paparan lebih rendah dari 0,25 mR/Jam,sesuai SK Bapeten No.11/Ka-BAPETEN/VI-99 perisai beton dibuat menjadi tebal 1,5 m